”—Registered nurses’ experiences of leading home care workers caring for dying individuals in their last days of life: A content analysis study - Laura Tolboom; Ulla Näppä; Lisbeth Kristiansen (Palliative Care and Social Practice)
Background: A mayority of individuals suffering from life-threatening diseases prefer a home death. Registered nurses (RNs) in home healthcare (HHC) play a crucial role in providing this care, as they are responsible for the caregiving process by leading home care workers (HCWs) who provide bedside care, constituting a complex collaboration. However, the research available on this topic, with a focus on nurse leadership, is rather limited. Objective: This study aimed to explore RNs’ experiences of leading HCWs who were caring for dying individuals in the last days of life. Design: A qualitative, descriptive, and inductive design was utilized with the help of focus group interviews (FGIs), which involved interviewing 20 RNs employed in HHC in northern Sweden. The FGIs were then analyzed using qualitative content analysis. Results: The RNs found that a solid working relationship between themselves and HCWs is important to ensure high-quality care in the last days of a patient’s life. They aimed to be available to HCWs and guide them on how to anticipate the dying process and felt responsible for supporting them, often putting their own needs last. The RNs longed for support and guidance themselves while developing their teams. They led HCWs in their development, emphasizing that care in the last days of life was specifically multifaceted, complex, and demanding. Language barriers, organizational challenges, and unclear delineations of leadership responsibilities complicated RNs’ leadership in relation to HCWs. Conclusion: The RNs favored relational leadership styles, but they faced numerous challenges that varied between urban and rural areas. Moreover, the RNs led by example in dealing with existential feelings, providing care, ensuring symptom management, and fostering communication and teamwork. Through their leadership, marked by compassion and empowerment, they aimed to enhance the quality of care and nurture a supportive network essential for navigating care in patients’ last days of life.